Climatic, topographic, and local-scale variables differently shape bird communities in urban streets and parks - Lucas M. Leveau (Avian Research, 2025)
Green cover and human disturbance are important local factors shaping urban bird communities, while climatic and topographic variables can be important when analyzing cities in different biomes. However, the roles of large-scale and local variables influencing bird species composition have been scarcely explored in urban areas. This study aimed to analyze the association of climatic, topographic, landscape, and local variables with bird species composition in streets dominated by buildings and urban parks. I expected park bird composition to be more related to large-scale variables, whereas bird species in streets to be more associated with local-scale variables. Bird surveys were conducted in nine cities along a climatic and topographic gradient. Bird species composition in urban parks and streets were related to climatic and topographic variables, local vegetation greenness, and distance to non-urban areas. However, bird composition in streets was also related to noise and pedestrian traffic. The classification of bird composition in urban parks aligned with the phytogeographic provinces, whereas the streets’ bird composition was unrelated to phytogeographic provinces. The results showed that urban habitats with increased vegetation cover allow the colonization of native bird communities and are more aligned with natural large-scale environmental gradients. In contrast, more urbanized sites are decoupled from climatic and topographic gradients and invaded by exotic and widespread native species.